Pengaruh Akuntabilitas, Moralitas Individu, Kesesuaian Kompensasi, Pengendalian Intern Dan Partisipasi Masyarakat Terhadap Potensi Fraud Dalam Pengelolaan Dana Desa - Adyaksana, Rahandhika Ivan; Lusmino Basia; Putri Wahyuni (Universitas PGRI Yogyakarta, 2024)
The research aims to examine effect of accountability, individual morality, suitability of compensation, internal control and community participation on potential for fraud in managing village funds. The population in this research is aimed at village officials in Playen Distict, Gunung Kidul Regency with a sample of 92 participants. Sampling was done by purposive sampling method. The data use is primary. Analysis research data use multiple linear regression. Based on test results, it shows that the variables of accountability (X1), individual morality (X2), suitability of compensation (X3), internal control (X4) and community participation (X5) have a negative influence on potential for fraud in village fund management (Y).